Diseño e implementación del departamento de comunicación en el Gobierno Autónomo Descentralizado de la Parroquia Rural de Guayllabamba (GAD-Guayllabamba). - Andagoya Ortega, Johanna Nathaly (2014)
This research proposes a design and implementation of the Department of Communication at the Autonomous Decentralized Government rural parish of Guayllabamba. After extensive field research it was determined that the parish of Guayllabamba facing a serious problem of communication because it does not have any local media, or is involved in local development projects and community communication. This has led community unknown facts juncture of the parish, while it is evident that it is not an inclusive community, dialogue and citizen participation.